ダイ38ジ ナンキョク チイキ カンソクタイ ナツタイ ホウコク 1996-1997 - 山岸, 久雄; ヤマギシ, ヒサオ; Yamagishi, Hisao (2002)
P(論文) 第38次南極地域観測隊夏隊18名は越冬隊40名とともに1996年11月から1997年3月まで, 「しらせ」船上での観測, 昭和基地, ドームふじ観測拠点への物資輸送, 昭和基地での建設作業, 各種野外調査を行った。特に第V期5カ年計画の初年次にあたる今回, 観測系ではアムンゼン湾リーセル・ラルセン山地域での地質・地形調査, ドームふじ観測拠点での深層掘削と気象・大気観測のための物資輸送旅行など大規模の野外活動, 昭和基地では大型短波レーダーアンテナ建設など, 大型プロジェクトが並立していた。一方, 設営系では昭和基地整備10年計画(1991-2000年度)の一環としての新居住棟, 汚水処理棟の建設, 昭和基地初のローカルエリアネットワークの設置などが計画されていた。これらの計画がどのように実施されたかを報告する。 This report describes research and logistic activities of the summer party of the 38th Japanese Antarctic Research Expedition carried out November 1996-March 1997. The research activities consist of large projects such as geological and geographical research in the Mt. Riiser-Larsen area adjacent to Amundsen Bay; an inland traverse to Dome Fuji Station, 1000km from Syowa Station, to transport wintering members and supplies for deep ice-core drilling and meteorological observations; and installation of an HF radar system at Syowa Station to observe ionospheric plasma convection. The logistic activities include major works such as construction of the new Accommodation Building for the wintering members, the Sewage Processing Building, and a local area network in Syowa Station. departmental bulletin paper